Organizational change : creating change through strategic communication - Lewis, Laurie K. (Foundations of communication theory, 2011)
"What is organizational change and how it can be brought about? Organizational Change integrates major empirical, theoretical and conceptual approaches to implemented communication in organizational settings. Laurie Lewis ties together the disparate literatures in management, education, organizational sociology, and communication to explore how the practices and processes of communication work in real-world cases of change implementation. Written for both undergraduate and graduate students, the book fills in an important piece of the applied communication puzzle as it relates to organizations. In addition to giving a bold and comprehensive overview of communication research and ideas on change and those who bring it about, each chapter is illustrated with student friendly, real life case studies from organizations, including organizational mergers, governmental or nonprofit policy or procedural implementation, or technological innovation."--